Hematite Photoanode with Complex Nanoarchitecture Providing Tunable Gradient Doping and Low Onset Potential for Photoelectrochemical Water Splitting. Issue 11 (26th April 2018) - Ahn, Hyo‐Jin; Goswami, Anandarup; Riboni, Francesca; Kment, Stepan; Naldoni, Alberto; Mohajernia, Shiva; Zboril, Radek; Schmuki, Patrik
Abstract: Over the past years, α‐Fe2 O3 (hematite) has re‐emerged as a promising photoanode material in photoelectrochemical (PEC) water splitting. In spite of considerable success in obtaining relatively high solar conversion efficiency, the main drawbacks hindering practical application of hematite are its intrinsically hampered charge transport and sluggish oxygen evolution reaction (OER) kinetics on the photoelectrode surface. In the present work, we report a strategy that synergistically addresses both of these critical limitations. Our approach is based on three key features that are applied simultaneously: i) a careful nanostructuring of the hematite photoanode in the form of nanorods, ii) doping of hematite by Sn 4+ ions using a controlled gradient, and iii) surface decoration of hematite by a new class of layered double hydroxide (LDH) OER co‐catalysts based on Zn–Co LDH. All three interconnected forms of functionalization result in an extraordinary cathodic shift of the photocurrent onset potential by more than 300 mV and a PEC performance that reaches a photocurrent density of 2.00 mA cm −2 at 1.50 V vs. the reversible hydrogen electrode. Abstract : Three routes, one goal : A strategy is described to address the drawbacks of the hematite photoanode for photoelectrochemical (PEC) water splitting that includes: i) nanostructuring of the hematite photoanode into nanorods, ii) Sn 4+ controlled‐gradient doping of the hematite layer, and iii) hematite surface decoration with Zn–Co‐based layered double hydroxide co‐catalysts. These modifications result in a cathodic shift of the photocurrent onset potential and improved PEC performance.